Simulation technologies in networking and communications: selecting the best tool for the test - Pathan, Al-Sakib Khan (CRC Press, Taylor & Francis Group, USA, 2015)
Simulation is a widely used mechanism to validate the theoretical model of networking or communication systems. It is believed that claims made based on simulations are more or less reliable—at least in the sense that something beyond theory is provided. But, how reliable simulation technologies really are is a question asked when the practicality is evaluated with real-world implementation trials. It is a fact that all simulators for the same system do not have the same inherent working method. Different simulators developed for networking and communications technologies have different underlying mechanisms that may significantly affect the simulation scenarios. The same scenario could give different results if different simulators are used for evaluation. Hence, the question “which one is the best for which situation?” is raised. There is no clear verdict on this issue. Therefore, the selection of a particular simulator should be left for the researcher to decide, if that shows relatively better results for his system or model or proposed solution. From this perspective, simulation is considered as something better than nothing to validate a claim or to show something to establish a ground for the proposal. A practical scenario could be, again, very much different and a theoretical model may often be a more solid proof than simulations in the sense that theory would prove the core idea with a solid foundation, and then it would be left for practical testing and performance measurement.